Strategic Development Associated with Branding in the Tourism Sector: Bibliometric Analysis and Systematic Review of the Literature between the Years 2000 to 2022. - López-Rodríguez, Campo Elías; Mora Forero, Jorge Alexander; León-Gómez, Ana María (MDPI, 2022)
This study aims to identify research trends associated with the development of brand management in the tourism sector. To this end, bibliometric analysis has been carried out, using the R Core Team 20201-Bibliometrix software, on the scientific production, the most influential countries, authors, and journals, and the co-occurrence of keywords in the 1421 articles published to date in the Scopus database. This analysis was then complemented with a systematic qualitative evaluation using the PRISMA technique. The results obtained show the trend and impact of the literature published to date and the established and emerging research groups. Furthermore, they identify that research procedures related to brand communities, co-branding, brand architecture, positioning, and brand research in the tourism sector need to be strengthened. Therefore, this study identifies key research questions in a way that provides a planning framework for future research in this field.
Keywords: Turismo; Marketing; Planificación estratégica; Branding; Tourism; Bibliometrics; Brand value